2021
DOI: 10.5194/se-12-79-2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of basal drag on subduction dynamics from 2D numerical models

Abstract: Abstract. Subducting slabs are an important driver of plate motions, yet the relative importance of different forces in governing subduction motions and styles remains incompletely understood. Basal drag has been proposed to be a minor contributor to subduction forcing because of the lack of correlation between plate size and velocity in observed and reconstructed plate motions. Furthermore, in single subduction system models, low basal drag leads to subduction behaviour most consistent with the observation th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Some previous numerical modeling studies suggest that viscous drag along the base of the overriding plate lithosphere controls the back‐arc stress field (e.g., Capitanio et al., 2011; Dal Zilio et al., 2018; Holt et al., 2015; Sleep & Toksoz, 1971; Suchoy et al., 2021). The basal drag force in our models is following Billen (2008) approximated by Fbd=2vdiffwµmlLop where v diff ∼ 5 cm year −1 is the velocity difference between overriding plate and the underlying mantle, μ ml ∼ 1 × 10 19 to 1 × 10 20 Pa s the viscosity of the upper mantle at the LAB, L op ∼ 1,500 km the width of the overriding plate, and the same length scale related to the velocity difference that was used for estimating Fvd (Lop = 100 km; after Billen, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous numerical modeling studies suggest that viscous drag along the base of the overriding plate lithosphere controls the back‐arc stress field (e.g., Capitanio et al., 2011; Dal Zilio et al., 2018; Holt et al., 2015; Sleep & Toksoz, 1971; Suchoy et al., 2021). The basal drag force in our models is following Billen (2008) approximated by Fbd=2vdiffwµmlLop where v diff ∼ 5 cm year −1 is the velocity difference between overriding plate and the underlying mantle, μ ml ∼ 1 × 10 19 to 1 × 10 20 Pa s the viscosity of the upper mantle at the LAB, L op ∼ 1,500 km the width of the overriding plate, and the same length scale related to the velocity difference that was used for estimating Fvd (Lop = 100 km; after Billen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the estimates of slab‐pull and interface resistance, viscous drag is thus unlikely to play a critical role influencing the back‐arc stress field in our models. It should be noted that with higher viscosities in the sublithospheric mantle and larger plates, viscous drag can become a significant actor (e.g., Dal Zilio et al., 2018; Suchoy et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, which consider it to be a layer of partial melt, suggest that it is only 10-20 km thick (Sakamaki et al, 2013;Schmerr, 2012;Stern et al, 2015), whereas others advocate for a layer extending from the lithosphere-asthenosphere boundary up to 200-300 km depth (thus a thickness of approximately 100-200 km) (Barruol et al, 2019;Becker, 2017;Debayle et al, 2020;French et al, 2013;Kawakatsu et al, 2009;Paulson & Richards, 2009). Here, we simulate the presence of the WAL by imposing a viscosity reduction between the 1,100°C isotherm (a proxy for the LAB) and a depth of 220 km, similarly to Suchoy et al (2021). Note that models tested with a WAL extending up to 300 km depth showed little differences with the results reported below.…”
Section: Treatment Of Walmentioning
confidence: 99%
“…The presence of a WAL is predicted to affect large-scale dynamics of the underlying, convecting mantle (Lenardic et al, 2006), and to favor "plate-like" rather than "stagnant-lid" regimes (Höink et al, 2012). Since the sub-lithospheric mantle resists a plate's trenchward motion, the inclusion of a WAL in models of subduction dynamics yields faster subduction velocities v sp , as shown by Carluccio et al (2019) and Suchoy et al (2021). The latter authors also showed that increased v sp was coeval with reduced trench retreat v t , although they did not detail the implications for lower mantle slab morphologies.…”
mentioning
confidence: 99%